Enhancing High School Students’ Paragraph Coherence Through Peer Feedback in English Writing - Maulana Arief Hidayat Hidayat (EXPOSE (Journal of English Education and for Specific Purpose), 2025)
Paragraph coherence is a critical aspect of effective writing, yet many high school students struggle to organize ideas logically in English as a Foreign Language (EFL) contexts. This study aims to examine the effect of structured peer feedback on paragraph coherence and to explore students’ perceptions of the feedback process. A mixed-method design was employed, involving 28 eleventh-grade students at SMK Muhammadiyah Pringsewu. Quantitative data were collected through pre-test and post-test paragraph coherence scores, while qualitative data were obtained from students’ reflective journals and interviews. The quantitative results indicate a significant improvement in paragraph coherence, with mean scores increasing from 2.65 in the pre-test to 4.15 in the post-test, particularly in topic sentence clarity, logical sequencing, and the use of cohesive devices. Qualitative findings reveal that students perceived peer feedback as enhancing their awareness of paragraph structure, promoting self-monitoring, reducing writing anxiety, and increasing motivation to revise their work. These findings suggest that structured peer feedback not only improves measurable writing outcomes but also fosters cognitive, metacognitive, and affective development. Based on the results, it is recommended that EFL teachers integrate structured peer feedback into writing instruction, providing guided opportunities for collaborative review, reflective practice, and targeted guidance on coherence. Such practices can enhance both the quality of students’ writing and their engagement in the learning process.